2019
DOI: 10.3390/ijms20246242
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Differentiation of Human Adipose Tissue-Derived MSCs by Non-Toxic Calcium Poly(ethylene phosphate)s

Abstract: P.I.) 2 A.V. Topchiev Institute of Petrochemical Synthesis RAS, 29 Leninsky Pr.,Abstract: There is a current clinical need for the development of bone void fillers and bioactive bone graft substitutes. The use of mesenchymal stem cells (MSCs) that are seeded into 3D scaffolds and induce bone generation in the event of MSCs osteogenic differentiation is highly promising. Since calcium ions and phosphates promote the osteogenic differentiation of MSCs, the use of the calcium complexes of phosphate-containing pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Cholesterol-initiated PEPA/poly(EtOEP) copolymer demonstrated no hemolysis activity or cytotoxicity against MC3T3-E1 cells [ 80 , 89 ]. No cytotoxicity was detected during experiments on adipose-tissue-derived multipotent mesenchymal stem cells (ADSCs) adhesion and proliferation in the presence of Na and Ca salts of PEPA [ 125 ] ( Figure 10 ).…”
Section: Properties and Applications Of Polyphosphodiestersmentioning
confidence: 99%
“…Cholesterol-initiated PEPA/poly(EtOEP) copolymer demonstrated no hemolysis activity or cytotoxicity against MC3T3-E1 cells [ 80 , 89 ]. No cytotoxicity was detected during experiments on adipose-tissue-derived multipotent mesenchymal stem cells (ADSCs) adhesion and proliferation in the presence of Na and Ca salts of PEPA [ 125 ] ( Figure 10 ).…”
Section: Properties and Applications Of Polyphosphodiestersmentioning
confidence: 99%
“…We have recently developed an approach to synthesis of PEPAs and PEPA-based block copolymers [ 29 ] and demonstrated their biocompatibility [ 41 ]. Hypothetically, salts formed by by TFV base with such copolymers offer an opportunity to regulate the rate of TFV release by varying the length of PEPA chains and acid to base molar ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Copolymers of poly(ethylene phosphoric acid)s (PEPA) that can be obtained by different methods [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], are polyacids potentially able to bind and deliver organic bases, including drugs. Despite the obvious promise of PEPA for different biomedical applications [ 27 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 ], the ability of PEPA-containing polymers to act as a carrier of antiviral drugs with basic functional groups have not been studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…Nifant'ev et al [35] also recently reported the enhancement of osteoblastic differentiation by PPDEs. They synthesized PEP via the route shown in Figure 2b and made the polysalts PEP•Na and PEP•Ca in the aqueous phase.…”
Section: Osteoblast Differentiationmentioning
confidence: 91%